## Equation: (x-1)/(3x-6)+(2x-1)/(2-x)-(x-3)(4x-8)=1

Quadratic equations and inequalities, variation equations, function notation, systems of equations, etc.
pieldevereda
Posts: 6
Joined: Fri Mar 11, 2011 2:25 pm
Contact:

### Equation: (x-1)/(3x-6)+(2x-1)/(2-x)-(x-3)(4x-8)=1

Hi, i can 't resolve this exercise

$\frac{x\, -\, 1}{3x\, -\, 6}\, +\, \frac{2x\, -\, 1}{2\, -\, x}\, -\, \frac{x\, -\, 3}{4x\, -\, 8}\, =\, 1$

The result is 41/35 but i don 't why

thanks

regards

Martingale
Posts: 333
Joined: Mon Mar 30, 2009 1:30 pm
Location: USA
Contact:

### Re: Equation: (x-1)/(3x-6)+(2x-1)/(2-x)-(x-3)(4x-8)=1

Hi, i can 't resolve this exercise

$\frac{x\, -\, 1}{3x\, -\, 6}\, +\, \frac{2x\, -\, 1}{2\, -\, x}\, -\, \frac{x\, -\, 3}{4x\, -\, 8}\, =\, 1$

The result is 41/35 but i don 't why

thanks

regards
$\frac{x-1}{3x-6}+\frac{2x-1}{2-x}-\frac{x-3}{4x-8}=1 \Leftrightarrow$

$\Leftrightarrow\frac{x-1}{3(x-2)}+\frac{2x-1}{(-1)(x-2)}-\frac{x-3}{4(x-2)}=1$

$\Leftrightarrow\frac{(-4)(x-1)+(12)(2x-1)-(-3)(x-3)}{-12(x-2)}=1$

$\Leftrightarrow\frac{23x-17}{-12(x-2)}=1\Leftrightarrow \cdots$

pieldevereda
Posts: 6
Joined: Fri Mar 11, 2011 2:25 pm
Contact:

### Re: Equation: (x-1)/(3x-6)+(2x-1)/(2-x)-(x-3)(4x-8)=1

Hi Martingale, thanks for your answer, but i don 't understand why appears the "(-1)" in 2x-1 / (-1) ( x-2)

Thanks Again
REgards

Martingale
Posts: 333
Joined: Mon Mar 30, 2009 1:30 pm
Location: USA
Contact:

### Re: Equation: (x-1)/(3x-6)+(2x-1)/(2-x)-(x-3)(4x-8)=1

Hi Martingale, thanks for your answer, but i don 't understand why appears the "(-1)" in 2x-1 / (-1) ( x-2)

Thanks Again
REgards

$2-x=-(-2+x)=-(x-2)=(-1)(x-2)$